New Arrivals: An Indicator for Non-indigenous Species Introductions at Different Geographical Scales - Olenin, Sergej; Narščius, Aleksas; Gollasch, Stephan; Lehtiniemi, Maiju; Marchini, Agnese; Minchin, Dan; Srėbalienė, Greta (Frontiers in Marine Science, 2016)
Several legal and administrative instruments aimed to reduce the spread of non-indigenous species, that may pose harm to the environment, economy and/or human health, were developed in recent years at international and national levels, such as the International Convention for the Control and Management of Ship’s Ballast Water and Sediments, the International Council for the Exploration of the Sea Code of Practice on the Introductions and Transfers of Marine Organisms, the EU Regulation on Invasive Alien Species and the Marine Strategy Framework Directive, the US Invasive Species Act, the Biosecurity Act of New Zealand, etc. The effectiveness of these instruments can only be measured by successes in the prevention of new introductions. We propose an indicator, the arrival of new non-indigenous species (nNIS), which helps to assess introduction rates, especially in relation to pathways and vectors of introduction, and is aimed to support management. The technical precondition for the calculation of nNIS is the availability of a global, continuously updated and verified source of information on aquatic non-indigenous species. Such a database is needed, because the indicator should be calculated at different geographical scales: 1) for a particular area, such as port or coast of a country within a Large Marine Ecosystem (LME); 2) for a whole LME; and 3) for a larger biogeographical region, including two or more neighboring LMEs. The geographical scale of nNIS helps to distinguish between a primary introduction and secondary spread, which may involve different pathways and vectors. This, in turn, determines the availability of management options, because it is more feasible to prevent a primary introduction than to stop subsequent secondary spread. The definition of environmental target, size of assessment unit and possible limitations of the indicator are also discussed.